Effect of Zn Supplemented to Immune Status Premenopausal Women Intervented with Isoflavoned Drinking - HERY WINARSI; DEDDY MUCHTADI; FRANSISKA RUNGKAT ZAKARIA; AGUS PURWANTO (Bogor Agricultural University, Indonesia, 2005)
The research was conducted to find out the effect of Zn supplement to immune status of premenopausal women intervented with isoflavoned drinking. Respondents were 22 women, more than 40 year of age. They were divided into two groups, i.e. 11 women intervented with isoflavone, and other 11 women intervented with isoflavone and 8 mg Zn. The activities of SOD, catalase and GPX were determined by spectrophotometer, thymulin levels by ELISA, whereas Zn levels by AAS. Result showed that Zn had significantly increased SOD lymphocyte activities (p=0.002) and thymulin plasma (p=0.011). Zn had increased catalase (p=0.103) and GPX (p=0.322) as well, but Zn plasma had decreased (0.163). It was indicated that Zn had improved the immune status by increasing lymphocyte and thymus cells activities.